Politics and Pluralism: Analyzing State Official Tafsir and Interfaith Discourse in Indonesia - Mursyid, Achmad Yafik; AlBaihaqi, Muhammad Dzilfikri; Murtafi'ah , Alvy Ra'isatul (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2024)
This research aims to explore the Tafsir produced by the Ministry of Religious Affairs of the Republic of Indonesia, specifically focusing on the potential politicization of the Qur’an, particularly in the narrative of inter-religious relationships in Indonesia. The study underscores the crucial role of Tafsir in shaping societal perceptions of religious pluralism in the country. In this context, a significant question arises concerning the extent to which the interpretations generated through the state's political mechanisms contribute to the discourse on religious pluralism. To address this inquiry, the critical discourse analysis approach by Norman Fairclough is employed, encompassing three dimensions: text analysis, discursive practices, and social practices. The analysis focuses on the Tafsir produced in 1980 by the Indonesian Ministry of Religious Affairs titled "Al-Qur’an dan Tafsirnya." The research reveals that the narrative regarding inter-religious relationships in Indonesia within the official Tafsir is not solely connected to the state's role through the Ministry of Religious Affairs of Indonesia. It is also influenced by various factors such as the socio-religious context and the role of Mufassir (mufasir). This situation is reflected through three patterns of state affirmation: Affirmative-Accommodative, Affirmative-Permissive, and Affirmative-Disruptive. The substantial contribution of this research lies in enhancing the understanding of the intricate relationship between religious exegesis, state politics, and radicalism in Indonesia. This opens avenues for further reflection and debate in scholarly literature, particularly regarding the impact of state involvement in the Qur’an interpretation process on the narrative of inter-religious relationships in Indonesia.